Transcriptomic stability or lability explains sensitivity to climate stressors in coralline algae - Tessa M. Page; Carmel McDougall; Ido Bar; Guillermo Diaz-Pulido (BMC Genomics, 2022)
Abstract Background Crustose coralline algae (CCA) are calcifying red macroalgae that play important ecological roles including stabilisation of reef frameworks and provision of settlement cues for a range of marine invertebrates. Previous research into the responses of CCA to ocean warming (OW) and ocean acidification (OA) have found magnitude of effect to be species-specific. Response to OW and OA could be linked to divergent underlying molecular processes across species. Results Here we show Sporolithon durum, a species that exhibits low sensitivity to climate stressors, had little change in metabolic performance and did not significantly alter the expression of any genes when exposed to temperature and pH perturbations. In contrast, Porolithon onkodes, a major coral reef builder, reduced photosynthetic rates and had a labile transcriptomic response with over 400 significantly differentially expressed genes, with differential regulation of genes relating to physiological processes such as carbon acquisition and metabolism. The differential gene expression detected in P. onkodes implicates possible key metabolic pathways, including the pentose phosphate pathway, in the stress response of this species. Conclusions We suggest S. durum is more resistant to OW and OA than P. onkodes, which demonstrated a high sensitivity to climate stressors and may have limited ability for acclimatisation. Understanding changes in gene expression in relation to physiological processes of CCA could help us understand and predict how different species will respond to, and persist in, future ocean conditions predicted for 2100.